The Role of The Community in Handling The Covid-19 Pandemic in Indonesia - Abdul Rohim (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Coronavirus disease is also known as Covid-19 (Corona Virus Disease 2019) and was discovered in the city of Wuhan, China at the end of December 2019. This virus spreads rapidly and has reached almost every country, including Indonesia, in just a few months. As a result, numerous countries have implemented regulations imposing lockdowns to prevent the spread of the Coronavirus. To control the spread of this virus, Indonesia implemented a Large-Scale Social Restriction (PSBB) policy. The method employed in this study is to analyze data from various reading sources. By comparing journals or articles, references are obtained from online publications with diverse studies. This study utilized five journals as references, all of which demonstrated that community participation in preventing the spread of Covid-19 was in a good category. According to the journals reviewed, information regarding the handling of Covid-19 necessitated the participation of all parties to prevent its spread. From the five journals obtained, all of these journals indicate that the role of the community is required in preventing the spread of the Covid-19 virus.